Key concepts in drugs and society - Coomber, Ross, (SAGE key concepts., 2013)
"Insightful and illuminating, this book successfully discusses drugs in social contexts. In an elegant manner, the authors bring together their different theoretical and practical backgrounds, offering a comprehensive and interdisciplinary introduction that opens up a wide scientific understanding moving beyond cultural myths and presuppositions. This is an invaluable reference source for students on criminology, sociology and social sciences programmes, as well as drug service practitioners such as drug workers, social workers and specialist nurses"--Publisher's website.